Functional assessment of hydrophilic domains of late embryogenesis abundant proteins from distant organisms. Issue 4 (22nd April 2019) - Liu, Yingying; Zhang, Heng; Han, Jiahui; Jiang, Shijie; Geng, Xiuxiu; Xue, Dong; Chen, Yun; Zhang, Chen; Zhou, Zhengfu; Zhang, Wei; Chen, Ming; Lin, Min; et al.
Summary: Late embryogenesis abundant (LEA) proteins play a protective role during desiccation and oxidation stresses. LEA3 proteins are a major group characterized by a hydrophilic domain (HD) with a highly conserved repeating 11‐amino acid motif. We compared four different HD orthologs from distant organisms: (i) DrHD from the extremophilic bacterium Deinococcus radiodurans ; (ii) CeHD from the nematode Caenorhabditis elegans ; (iii) YlHD from the yeast Yarrowia lipolytica ; and (iv) BnHD from the plant Brassica napus . Circular dichroism spectroscopy showed that all four HDs were intrinsically disordered in phosphate buffer and then folded into α‐helical structures with the addition of glycerol or trifluoroethanol. Heterologous HD expression conferred enhanced desiccation and oxidation tolerance to Escherichia coli . These four HDs protected the enzymatic activities of lactate dehydrogenase (LDH) by preventing its aggregation under desiccation stress. The HDs also interacted with LDH, which was intensified by the addition of hydrogen peroxide (H2 O2 ), suggesting a protective role in a chaperone‐like manner. Based on these results, the HDs of LEA3 proteins show promise as protectants for desiccation and oxidation stresses, especially DrHD, which is a potential ideal stress‐response element that can be applied in synthetic biology due to its extraordinary protection and stress resistance ability. Abstract : We first characterized four putative HDs that were indispensable to G3LEA protein function undergoing structural transformation and providing chaperone‐like protection. The great performance of DrHD encouraged us to continue exploring its specificity and the hidden robustness of the G3LEA proteins, and inspired us to look for brief functional elements in future work for biosynthetic applications.